Repair of bileaflet prolapse in Barlow syndrome: The 4‐chord technique. Issue 7 (17th May 2019) - Chemtob, Raphaelle A.; Mick, Stephanie; Gillinov, Marc; Hodges, Kevin; Wierup, Per
Abstract: Barlow syndrome is a form of degenerative mitral valve (MV) disease found in a subset of patients with bileaflet prolapse. The hallmark of Barlow's disease includes excessive and billowing leaflet tissue caused by myxomatous tissue proliferation, elongated chordae, and pronounced annular dilatation. Surgical repair of patients with Barlow's disease is challenging due to the extent of the leaflet and annular abnormalities. Several techniques have been described to repair Barlow's MV including currently popular "non‐resectional" approaches. Repair with neochordae has been associated with excellent results and includes the advantage of preserved leaflet mobility and a large surface of coaptation. We describe a simple approach to the use of neochordae to repair bileaflet prolapse in patients with Barlow syndrome and avoid systolic anterior motion.